"FILL AND SUBDUE"? IMAGING GOD IN NEW SOCIAL AND ECOLOGICAL CONTEXTS. Issue 1 (March 2015) - Roberts, Jason P.
Abstract While the social and ecological landscape of the twenty‐first century is worlds away from the historical‐cultural context in which the biblical myth‐symbols of the image of God and the knowledge of good and evil first emerged, Philip Hefner's understanding that Homo sapiens image God as created co‐creators presents a plausible starting point for constructing a second naïveté interpretation of biblical anthropology and a fruitful concept for envisioning and enacting our human future.